An In Vitro Study of Different Extracts and Fractions of Allium sativum (Garlic): Vascular Reactivity - Patricia Ganado; Mercedes Sanz; Eugenia Padilla; Teresa Tejerina (Elsevier, 2004)
The aim of this study was to investigate the effect of different novel extracts and fractions obtained from Allium sativum (garlic) on in vitro vessel contraction in order to deepen our knowledge of their mechanism of action on vascular reactivity. The contraction induced by noradrenaline (NE, 10-6 or 10-5 M) or KCl (80 mM) was relaxed with all the extracts and fractions studied, but this effect was higher with RG 20-100 (raw garlic fraction) and FG 20-100 (frozen garlic fraction). To increase our understanding of the mechanisms of action of RG 200-100 and FG 200-100, we found their inhibitory actions were retained in the absence of endothelium, whereas inhibition of the entry of extracellular calcium and mobilization of intracellular calcium may play an instrumental role. Keywords:: Allium sativum (garlic), vascular reactivity, aorta, mesenteric artery (4th branch)